Quantity surveying practice : the nuts and bolts - Keung, Chung Wai Calvin; Yeung, Kam Lan Daisy; Cheung, Sai On (New York Fordham University Press, 2019)
"This practical book focuses on the basic concepts underlying the technical aspects of quantity surveying and contains many worked examples together with useful figures and real-life cases to help readers digest and understand the essentials and become better professionals as a result"--
Includes bibliographical references and index.
Keywords: Quantity surveying